Special Protection For Whistleblowers In Disclosing Money Laundering In Indonesia - Hasbi, Mhd.; Ansari, Ansari; Hamdani, Muhammad Faisal (SASI, 2023)
Introduction: A suspected criminal act of money laundering or a person who is designated as a witness in the process of examining a criminal act of laundering is obliged to obtain protection from the state. Purposes of the Research:  This paper aims to find out the criminal law aspects of reporting Money Laundering where in fact someone as a reporter usually turns into a suspect so that this paper gives the spirit and courage of the community as a reporter because it is protected by state law.Method Of The Research:  The type of research is normative juridical with analysis using legal documents in the form of primary legal materials, secondary legal materials, and tertiary legal materials. Results of the Research : Reporting of suspected money laundering or a person who is designated as a witness in the process of investigating a laundering crime is mandatory to obtain protection from the state. The protection given to reporters and witnesses is given in two forms, namely legal protection and special protection.